(untitled) (Eurasian Medical Research Periodical, 2022)
Hip arthroscopy is a procedure in which some diseases that were traditionally performed by open surgery are attempted to be corrected. It is a technically complex and generally long-term procedure. Femorofemoral impingement is the most common disease and has various causes that lead to it. This paper aims to know the role of anesthesia on patients who underwent hip arthroscopy between 20-55 ages. A specific questionnaire was applied to 120 patients, 70 general anesthesia with aged between 25 and 50 years from several different hospitals and 50 rigional anesthesia between 25 and 50 years. A questionnaire was designed by experts from the Hip Arthroscopy Technical Group of the Ministry of Public Health, and a database was created using Microsoft Access The result which found in this paper were (120 cases collected divided to general anesthesia (N=70), where 25 were male and 45 were female for general anesthesia, while Rigional anesthesia (N=50), where 18 were male and 32 female). The study revealed a high body mass index for patients over the age of 33 years, 50 cases of patients were diagnosed with 64% of women patients group 34-50 kg/m2. Days of hospitalization, the median (IQR) for a patient with general anesthesia was 8 (6 to 10) days, and about rigional anesthesia was 6(4 to 8) In addition, most of the patients’ cases under general anesthesia were found to suffer from acute pain after surgery as compared with regional anesthesia in 45 cases with p< 0.05.